Placental morphology in pregnancies associated with pregravid obesity. (17th August 2016) - Loardi, Chiara; Falchetti, Marcella; Prefumo, Federico; Facchetti, Fabio; Frusca, Tiziana
Abstract: Objective : Pre-gravid obesity is associated with increased morbidity and mortality for both mother and offspring. We aimed to investigate the changes in placental structure and to characterize the placental inflammatory status in obese women. Methods : Placentas from 10 women with pregravid body mass index ≥ 30 kg/m 2 were analyzed histopathologically and compared with those from 10 normal weight women. The effect of pregravid obesity on placental structure was investigated by examining placental maturity, angiogenesis, inflammatory response, and vascular abnormalities. Hematoxylin and eosin stain, immunohistochemical analysis, and morphometric analysis were performed. Results : Immaturity of the villous tree was demonstrated more often in the pregravid obesity group ( p  = 0.005). The villous tree was mainly represented by villi of larger diameter ( p  = 0.001) and lower number ( p  = 0.023) compared with controls. By contrast, the number of capillaries per villus was increased in the obese group ( p  = 0.001), while the global number of capillaries per surface unit did not differ in the studied groups ( p  = 1). There was no difference between the pre-gravid obese group and controls in inflammatory status and vascular pathology. Conclusions : Pregravid obesity is associated with focal immaturity of the villous tree and angiogenetic abnormalities of the placenta.